2023
DOI: 10.3345/cep.2023.00563
|View full text |Cite
|
Sign up to set email alerts
|

Association between maternal coronavirus disease 2019 and transient tachypnea of the newborn: a single-center study

Sung Hee Lee,
Ju Hyun Jin,
Jong Ha Yoo
et al.

Abstract: Background: Limited clinical reports have investigated the effects of maternal coronavirus disease 2019 (COVID-19) on fetuses and neonates.Purpose: This retrospective study aimed to assess the impact of maternal COVID-19 on neonates during the perinatal period, including neonatal clinical outcomes, versus the outcomes of neonates of mothers without COVID-19.Methods: Neonates born to COVID-19-infected mothers at the National Health Insurance Service Ilsan Hospital between February 2021 and March 2022 were inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 32 publications
1
6
1
Order By: Relevance
“…Only 14 infants delivered by SARS-CoV-2 positive mothers were born prematurely. Therefore, the rate of prematurity was lower in mothers diagnosed with COVID-16 (6.42%) as compared to the prematurity rate during the study period (7.42%) and different from the rates reported by other authors: 7.4-26.8% [14,20,21,37,43,[55][56][57]. A lower rate (4.54%) was reported by a recent study performed during Omicron variant dominance [51].…”
Section: Discussioncontrasting
confidence: 71%
See 2 more Smart Citations
“…Only 14 infants delivered by SARS-CoV-2 positive mothers were born prematurely. Therefore, the rate of prematurity was lower in mothers diagnosed with COVID-16 (6.42%) as compared to the prematurity rate during the study period (7.42%) and different from the rates reported by other authors: 7.4-26.8% [14,20,21,37,43,[55][56][57]. A lower rate (4.54%) was reported by a recent study performed during Omicron variant dominance [51].…”
Section: Discussioncontrasting
confidence: 71%
“…Increased morbidity and mortality in pregnant women and newborns is recognized for many years with viral infections during pregnancy, therefore, even at the beginning of the pandemic both pregnant women and newborns were considered at high risk for SARS-CoV-2 infection and its complications. Soon after pandemic onset, reports coming first from China and thereafter from all over the world described adverse outcomes of COVID-19 during pregnancy: increased rates of prematurity, stillbirth, fetal death, intrauterine growth restriction (IUGR), fetal distress, maternal respiratory failure (with increased need for oxygen, respiratory support, and intensive care unit admission), preeclampsia, C-section delivery, and maternal and neonatal death as compared to non-exposed pregnancies [16][17][18][19][20][21][22][23][24]. Studies also reported an even more complicated course of COVID-19 in pregnancies complicated with lung, cardiovascular, renal, and liver conditions, high blood pressure, diabetes, obesity, anti-phospholipidic syndrome, and thrombophilia [9,25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study [ 4 ] compared the clinical outcomes between newborns born to mothers with COVID-19 who tested negative and those born to noninfected mothers (control group). The two groups were compared by matching gestational age at birth, and errors in the study results were reduced by regression analysis and controlling for other factors that may affect neonatal outcomes, including cesarean section.…”
mentioning
confidence: 99%
“…A significantly higher risk of transient tachypnea in the newborn, noninvasive ventilation use, and supplemental oxygen requirement were noted among neonates born to mothers with COVID-19. The authors emphasized the importance of closely monitoring respiratory symptoms in neonates born to COVID-19-infected mothers [ 4 ]. A Swedish study also reported that maternal SARS-CoV-2 infection during pregnancy was significantly associated with increased risk of respiratory disorders and other neonatal health issues [ 5 ].…”
mentioning
confidence: 99%